Printable and Flexible Planar Silver Electrodes-Based Resistive Switching Sensory Array - Tian, Xiyue; Luo, Zewei; Fan, Tianyi; Zhang, Jinjie; Chu, Junhao; Wu, Xing (Frontiers in Sensors, 2020)
With the advent of smart flexible electronic devices, new research directions have emerged. Among them, the resistive switching (RS) sensor has attracted much attention. The RS sensor converts the change of voltage signals into the change of resistance values. In this work, a planar flexible RS structure based on one-step printable silver electrodes was designed and fabricated to simplify device fabrication. The study is a starting point that paves the way for the development of all-in-one printable and flexible sensors in the future.